2007
DOI: 10.1136/ard.2007.072397
|View full text |Cite
|
Sign up to set email alerts
|

Decreased clinical response to infliximab in ankylosing spondylitis is correlated with anti-infliximab formation

Abstract: Objectives: Correlation of serum trough infliximab levels and antibodies to infliximab (anti-infliximab) with clinical response in ankylosing spondylitis. Methods: In accordance with the international ASsessment in Ankylosing Spondylitis (ASAS) consensus statement, patients were treated with infliximab (5 mg/kg) every 6 weeks after a starting regimen. Preinfusion sera were collected at baseline, 24 and 54 weeks. At every visit, the 20% improvement response (ASAS-20) was assessed and laboratory tests performed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
89
1
12

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(112 citation statements)
references
References 11 publications
10
89
1
12
Order By: Relevance
“…It is known that anti-TNF␣ therapy, especially infliximab, may induce antibody formation against the drug in patients with RA, and that concomitant MTX can prevent this antibody formation (25). Less is known about antibody formation against the anti-TNF␣ drugs in patients with PsA and AS, although a Dutch study recently demonstrated that clinical response to infliximab in patients with AS is also correlated to antiinfliximab antibody formation (26). Whether this can be prevented by concomitant immunosuppressive therapy is not known.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that anti-TNF␣ therapy, especially infliximab, may induce antibody formation against the drug in patients with RA, and that concomitant MTX can prevent this antibody formation (25). Less is known about antibody formation against the anti-TNF␣ drugs in patients with PsA and AS, although a Dutch study recently demonstrated that clinical response to infliximab in patients with AS is also correlated to antiinfliximab antibody formation (26). Whether this can be prevented by concomitant immunosuppressive therapy is not known.…”
Section: Discussionmentioning
confidence: 99%
“…de Vries и соавт. [20] показали, что концентрация ИНФ в сыворот-ке перед следующим введением у пациентов, ответивших на терапию, была достоверно выше, чем у не ответивших (p=0,018). При потере эффекта ИНФ возможна эскалация дозы препарата, однако четких доказательств увеличения концентрации препарата в сыворотке крови при этом не получено.…”
Section: Discussionunclassified
“…Иммуногенность препарата во многом зависит от структуры молекулы, химерные мАТ, к которым относится ИНФ, характеризуются более высокой иммуногенностью по сравнению с гуманизированными и полностью идентичны-ми человеческими мАТ [36]. Так, частота обнаружения анти-тел к препарату на фоне терапии ИНФ составляет от 12-44% у больных РА [36] до 29% у пациентов с АС [37]. По данным литературы, наличие антител к ИНФ у пациентов с АС кор-релирует с низким уровнем препарата в крови, снижением ответа на терапию и большим риском инфузионных реакций [37], хотя этот негативный эффект значительно менее выра-жен, чем при РА.…”
Section: иммуногенностьunclassified
“…Так, частота обнаружения анти-тел к препарату на фоне терапии ИНФ составляет от 12-44% у больных РА [36] до 29% у пациентов с АС [37]. По данным литературы, наличие антител к ИНФ у пациентов с АС кор-релирует с низким уровнем препарата в крови, снижением ответа на терапию и большим риском инфузионных реакций [37], хотя этот негативный эффект значительно менее выра-жен, чем при РА. В исследовании ASART-2 иммуногенность биоаналога и оригинального препарата была аналогичной, что коррелирует с данными многолетнего изучения ориги-нального ИНФ.…”
Section: иммуногенностьunclassified